Qu'est-ce que la philosophie africaine? - Lindon, Edward (2003)
This thesis traces the evolution of the concept of African philosophy through three phases: the cultural essentialism of Léopold Senghor, founder of Négritude, the universalist critical reaction of Paulin Hountondji and the professional philosophers, and the sophisticated particularism of Valentin Mudimbé. The three stages are contextualized with discussion of the socio-political positioning of each writer, his motives, and his particular understanding of what is at stake in the definition of African philosophy. The initial need to bring about a revalorization of African culture and a recognition of African philosophical capabilities is met by a flamboyant and highly vocal cultural movement, Négritude, which is, however, intrinsically limited in scope and lifespan, and sets up a number of persistent, dogmatic suppositions about the ‘essentially African reason’. A demonstration of the Western origins of this essentialism debunks but does not dispel its influence, since it is firmly anchored to the themes of authenticity, colonial influence, and postcolonial independence. This leads to a dilemma where any move to separate African philosophy from the notion of a distinctly African reason is perceived as a Eurocentric attempt at acculturation, or a capitulation to the false universalism of ‘Enlightenment philosophy’, and on the other hand, the view that African thought is essentially different from European thought is also criticized as deriving from the Western colonial discourse. There is no definitive answer to this problem, and even the search for such an answer is itself part of the problem, a further twist in the ruse that Mudimbé believes is inherent to the colonial discourse. The practical solution Mudimbé proposes is to introduce an écart between African scientific practice and the West, to create a new space within which Africans might investigate the field of their experience in an Afrocentric way which will preserve their cultural specificity.